Pengaruh Manajemen Aset, Pertumbuhan Penjualan, Leverage, Dan Ukuran Perusahaan Terhadap Kinerja Perusahaan (Jurnal Paradigma Akuntansi, 2022)
This study aims to obtain empirical evidence of the effect of asset management, sales growth, leverage, and firm size on firm performance in the manufacturing industries listed on the Indonesia Stock Exchange in 2017-2019. The research sample used was 36 companies with purposive sampling method based on criteria. The data processing technique uses multiple linear regression analysis assisted by the SPSS version 25 and Microsoft Excel 2010 program The results of this study indicate that asset management has a positive and significant effect on firm performance, sales growth does not have a significant effect on firm performance, leverage has a negative and significant effect on firm performance, and firm size has no significant effect on firm performance. The implication of this research is the need to pay attention to asset management, sales growth, leverage, and company size to improve company performance and as a consideration for decision making for investors.